Peptidases of pinworms Syphacia muris and Passalurus ambiguus - Vadlejch, Jaroslav; Lytvynets, Andriy; Jankovská, Ivana; Langrová, Iva (Experimental parasitology, 2010)
In this first report about pinworms peptidases we primarily characterize peptidases released during in vitro maintenance of two common pinworms of laboratory animals -Syphacia muris and Passalurus ambiguus. The peptidase activity obtained using sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) showed the presence of peptidases from S. muris with a wide range of molecular size (25-110 kDa), which degrades gelatin and mucin at alkaline pH levels. P. ambiguus released serine and aspartyl peptidases degrading gelatin at all tested pH (3, 5, 7, and 9) and at acidic pH Passalurus released aspartyl and cysteine peptidases which are active against mucin.
Keywords: Electrophoresis, Polyacrylamide Gel; Animals, Laboratory; elektroforéza v polyakrylamidovém gelu; Substrate Specificity; inhibitory proteas; Sulfones; Peptide Hydrolases; molekulová hmotnost; Female; Host-Parasite Interactions; krysa rodu Rattus; želatina; Oxyuroidea; zvířata; potkani Wistar; laboratorní zvířata; muciny; Edetic Acid; ženské pohlaví; Rats, Wistar; Male; substrátová specifita; Rabbits; sulfony; Gelatin; Hydrogen-Ion Concentration; oxyuriáza; králíci; Rats; Animals; mužské pohlaví; EDTA; koncentrace vodíkových iontů; interakce hostitele a parazita; Mucins; proteasy; Oxyuriasis; Protease Inhibitors; Molecular Weight